Marrow aspiration in aged mice: intramedullary osteogenesis, reduced mechano-adaptation, increased marrow fat. (4th March 2022) - Piet, Judith; Adamo, Sarah; Hu, Dorothy; Baron, Roland; Shefelbine, Sandra J.
ABSTRACT: Introduction: With age, the number of adipocytes and osteoclasts increases, the number of osteoblasts decreases, and mechano-adaptation is impaired. Objectives: Using marrow aspiration, which has a known osteogenic effect in young mice, we sought to recruit osteoblast progenitors to mediate the mechano-adaptive response to in vivo tibial loading. Methods: First, we assessed bone formation and marrow adiposity in the tibiae of old mice (>20 months) sacrificed 1, 2, and 4 weeks after unilateral marrow aspiration. Then, we examined the effects of marrow aspiration on mechano-adaptation in aged mice using tibial loading. Results: Two weeks after aspiration, aspirated tibiae had more bone than contralateral tibiae due to the formation of bone in the medullary canal. Two weeks and four weeks after marrow aspiration, the volume of marrow adipose tissue was higher in the aspirated tibiae, compared to contralateral tibiae. Histomorphometry indicated that aspiration increased non-periosteal (endosteal, intracortical, intramedullary) bone formation, compared to the contralateral tibia.  Mice with marrow aspiration had reduced periosteal bone formation in the contralateral tibia, compared to mice that had loading alone. Loading-induced periosteal bone formation was higher in mice that had loading alone, compared to mice that had aspiration + loading, indicating that aspiration further reduced the mechano-adaptive response. Conclusion: These data demonstrate that, in old mice, bone forms in the medullary canal following aspiration. Adiposity is increased following marrow aspiration, and periosteal mechano-adaptation is reduced.